2021
DOI: 10.3847/1538-4357/abdeb7
|View full text |Cite
|
Sign up to set email alerts
|

Massive White Dwarfs in Young Star Clusters

Abstract: We have carried out a search for massive white dwarfs (WDs) in the direction of young open star clusters using the Gaia DR2 database. The aim of this survey was (1) to provide robust data for new and previously known high-mass WDs regarding cluster membership, (2) to highlight WDs previously included in the initial final mass relation (IFMR) that are unlikely members of their respective clusters according to Gaia astrometry, and (3) to select an unequivocal WD sample that could then be compared with the host c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Fig. 3 shows the updated IFMR from Richer et al (2021) including these new escaped cluster member WDs as well as those identified in Heyl et al (2021a). Each of the three newly identified WDs from this work are more massive than any cluster WDs previously identified.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fig. 3 shows the updated IFMR from Richer et al (2021) including these new escaped cluster member WDs as well as those identified in Heyl et al (2021a). Each of the three newly identified WDs from this work are more massive than any cluster WDs previously identified.…”
Section: Discussionmentioning
confidence: 94%
“…The breadth of modern stellar surveys greatly expands our ability to search for these objects; in particular, the precise parallaxes and proper motions measured by the Gaia survey (Gaia Collaboration et al 2016) allow us to select high-confidence cluster members using only astrometry and photometry. Recently, a wide search for massive WDs in young clusters (Richer et al 2021) identified new young and high-mass WDs as cluster members, but failed to identify any cluster member WDs with masses in excess of 1.1 M or with progenitors over 6.2 M , leaving a gap in the high-mass region of the WD initial-final mass relation (IFMR).…”
Section: Introductionmentioning
confidence: 99%
“…An orthogonal direction to the ideas above is to apply these techniques to other nearby clusters. Richer et al (2021) have performed a search similar in spirit to the current one by looking for massive white dwarfs that escaped from more distant clusters. In their search, the relative proper motion of the cluster and the stars is considered and constrained to be small, but the time for the star to reach its current position or the inferred radial velocity did not play a role in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…One way to overcome these problems is to study white dwarfs in coeval systems like open clusters 6 (Kalirai et al, 2005;Dobbie et al, 2006;Kalirai et al, 2007;Cummings et al, 2018;Richer et al, 2021). The weak point in this case is that in order to compute the mass of white dwarfs it is necessary to obtain accurate spectra and this is only possible in the case of nearby open clusters.…”
Section: The Luminosity Functionmentioning
confidence: 99%